The Effect of The Learning Cycle 7E Model on Magnetic Field Materials to Improve Student's Deductive Reasoning - Munandar, Rizky; Gunawan; A., Syahrial (Mataram University, 2024)
Learning Cycle 7E is a model that is student-centered. Students must be active in the form of learning activities that are structured in such a way that they can master the material well. This research aims to test the effect of the Learning Cycle 7E model on magnetic field material to improve students' deductive reasoning. The type of research used was quasi-experimental with a one-group serial design. The population in this study was all class XII MIPA MAN 2 Mataram, with a sampling technique using purposive sampling, and class XII MIPA 1 was obtained as the experimental class. The data collection technique is a test consisting of 10 question items that have been validated and reliable. Based on the research results, students' levels of deductive reasoning were obtained with high, medium, and low criteria. Where the low criteria are 2 people, medium 29 people, and high 7 people. The results of the research show that the independent variable, namely the 7E learning cycle model, increases students' deductive reasoning abilities, with the highest score on the initial test being 71 while the lowest is 55. The highest score in the final test is 92 and the lowest is 77. Apart from that, seven phases contained in the learning model can also be used as well as possible, for example, students are given explanations for elicitation and engagement, and then students carry out exploration and explanation activities to elaborate their understanding after they are applied and in the last two phases students enter the evaluation phase. And material expansion or extension. This can also be proven based on the results of the N-Gain test with moderate and high gain with an average of 0.57.